IDENTIFIKASI PEMANFAATAN TRADISIONAL DAN PENAPISAN SENYAWA FITOKIMIA EKTRAK DAUN BINTANGUR (Callophyllum soulatri Burm F.) - Violet Violet (EnviroScienteae, 2018)
Bintangur (Callophylum soulatri) is one type of Family Callophylleae which is widely found in the forests of Borneo. This research attempts to identify the traditional using of Bintangur plant as a medicinal material and get the result of phytochemical compound from Bintangur leaf extract. Identification of the use of Bintangur plants is done using semi-structured interview techniques and literature review. The phytochemical compound preliminary test is carried out qualitatively by color change detection. Bintangur leaves can eliminate the disease vertigo (dizziness) and migraine. The dominant phytochemical compounds are flavonoids, steroid, and tannin. Phytochemical compounds that also dominant are phenol hydrocarbons and saponins. The alkaloid compound is not present in Bintangur leaves. The identification of phytochemical compounds from Bintangur leaf identifies the potential utilization of phytochemical compounds for various medicinal goals. The detection of steroid compounds with high concentrations indicates that Bintangur leaf has the potential to be used as a medicinal material to relieve chronic fatigue and pain. The presence of phenol compounds such as flavonoids, phenol hydrocarbons, and tannins indicates that the Bintangur leaf has bioactivity as antioxidants, antibacterials and anticancer.